Pharmacy law and ethics : For second year diploma pharmacy - Bagul, Vishal Suresh; Bari, Sanjaykumar B.; Patil, Rajeshwari Satish; Patil, Deepak Manohar (New Delhi CBS Publishers & Distributers, 2023)
b
Keywords: PHARMACEUTICAL JURISPRUDENCE